t-derivations in BP-algebras - Siswanti, T. Fuja; Gemawati, Sri; Syamsudhuha, Syamsudhuha (Lembaga Studi Pendidikan and Rekayasa Alam Riau, 2021)
BP-algebras is a non-empty set (X, *, 0) with the binary operation “*” satisfies the axioms (BP1) x * x = 0, (BP2) x * (x * y) = y, (BP3) (x * z) * (y * z) = x * y for all x, y, z = X . In this paper, we define the concept of (l, r) and (r, l) t-derivation in BP-algebra and investigate their properties. Based on the concepts of (l, r) and (r, l) t-derivation in BP-algebra, the properties of t-derivation in BP-algebra are constructed.